2012
DOI: 10.7202/1013420ar
|View full text |Cite
|
Sign up to set email alerts
|

Liminaire

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit. Érudit est un consortium interuniversitaire sans but lucratif composé de l'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Presence of mental health issues such as depression (Ahmedani et al, 2012;Arria et al, 2011;Encrenaz et al, 2012;Husky et al, 2012;Vasiliadis, Gagne, Jozwiak, & Preville, 2013;Wu et al, 2010), anxiety (Ahmedani et al, 2012;Arria et al, 2011;Encrenaz et al, 2012;Wu et al, 2010), and substance use (Encrenaz et al, 2012;Freedenthal, 2007;Routhier et al, 2012) were associated with greater help seeking behaviour among people with suicidality. In addition, severe suicidal intent (De Leo et al, 2005;Wong et al, 2014), history of suicidal ideation (Husky et al, 2012;McKibben et al, 2014;Pagura, Fotti, Katz, Sareen, & Tea, 2009), suicidal plans (Encrenaz et al, 2012;Husky et al, 2012), and suicidal attempts (Ballard et al, 2014;De Leo et al, 2005;Encrenaz et al, 2012;Freedenthal, 2007;McKibben et al, 2014;Milner & De Leo, 2010;Pagura et al, 2009) also facilitated help seeking behaviour.…”
Section: Professional Help Seeking Behaviour Among People With Suicidalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Presence of mental health issues such as depression (Ahmedani et al, 2012;Arria et al, 2011;Encrenaz et al, 2012;Husky et al, 2012;Vasiliadis, Gagne, Jozwiak, & Preville, 2013;Wu et al, 2010), anxiety (Ahmedani et al, 2012;Arria et al, 2011;Encrenaz et al, 2012;Wu et al, 2010), and substance use (Encrenaz et al, 2012;Freedenthal, 2007;Routhier et al, 2012) were associated with greater help seeking behaviour among people with suicidality. In addition, severe suicidal intent (De Leo et al, 2005;Wong et al, 2014), history of suicidal ideation (Husky et al, 2012;McKibben et al, 2014;Pagura, Fotti, Katz, Sareen, & Tea, 2009), suicidal plans (Encrenaz et al, 2012;Husky et al, 2012), and suicidal attempts (Ballard et al, 2014;De Leo et al, 2005;Encrenaz et al, 2012;Freedenthal, 2007;McKibben et al, 2014;Milner & De Leo, 2010;Pagura et al, 2009) also facilitated help seeking behaviour.…”
Section: Professional Help Seeking Behaviour Among People With Suicidalitymentioning
confidence: 99%
“…In addition, stigmatising attitudes towards mental health services also impeded people's help seeking behaviour (Czyz et al, 2013;De Leo et al, 2005;Downs & Eisenberg, 2012). Two quantitative studies reported prior treatment as a facilitator to help seeking behaviour (Arria et al, 2011;Milner & De Leo, 2010), although other studies suggest specific setting of treatments such as hospital emergency department (Routhier et al, 2012), level of satisfaction with prior treatment (Czyz et al, 2013;Strike et al, 2006), and whether the relationship between clients and medical helpers is consistent (Osvath, Michel, & Fekete, 2003) could also influence the role of prior treatment on help seeking.…”
Section: Professional Help Seeking Behaviour Among People With Suicidalitymentioning
confidence: 99%